2006
DOI: 10.1111/j.1540-8159.2006.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rate Control and Regularization Through Pacing in Patients With Chronic Atrial Fibrillation and Preserved Ventricular Function: The VRR Study

Abstract: VRR effectively stabilizes rate, without increasing pacing rate above spontaneous rhythm and helps achieve a more favorable autonomic balance, improving rate recovery after exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…1). 7 The patients were randomized using a randomization table at the time of implantation to receive a ventricular lead at either the RVA (passive‐fixation lead, Fig. 2A) or the RVS (active‐fixation lead, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 7 The patients were randomized using a randomization table at the time of implantation to receive a ventricular lead at either the RVA (passive‐fixation lead, Fig. 2A) or the RVS (active‐fixation lead, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous clinical studies demonstrated that ventricular overdrive pacing can regularize ventricular rate (VR) during atrial fibrillation (AF) to improve cardiac hemodynamic status 1–4 . However, the use of different ventricular overdrive pacing algorithms in patients with AF only demonstrated limited benefit on exercise capacity 5–7 . The potential benefit of VR regularization (VRR) may be offset by the adverse hemodynamic effects of right ventricular apical (RVA) 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The benefits of rate control achieved by activating VRR function is well established in patients with chronic AF and no or only mild HF treated with a single chamber right ventricular (RV) pacing. In these patients, VRR has been demonstrated to confer acute haemodynamic benefits, 16 to restore autonomic balance, 17 and to provide a more regular rhythm during exercise, 14 thus potentially improving functional status.…”
Section: Medical Therapeutical and Device-based Options For ‘Rate Conmentioning
confidence: 99%
“…Another useful feature is ‘ventricular sense response’ (also called ‘trigger’ function) which triggers LV pacing after a premature RV sense event is detected: 17 this option may be activated in all CRT devices of the latest generation.…”
Section: Medical Therapeutical and Device-based Options For ‘Rate Conmentioning
confidence: 99%